упрчстите выражение:

1) 6(a-2)(a-3)-4(a-3)^2;

2) (2x^2+x-5)^2-(2x^2+x)(2x^2+x-1)+9(2x^2+)

3) (m^2+n-4)^2-(m^2+n-1)(m^2+n-8)

1

Ответы и объяснения

  • Yena
  • главный мозг
2013-04-07T20:13:01+00:00

1) 6(a-2)(a-3)-4(a-3)²=6(a²-5a+6)-4(a²-6a+9)=6a²-30a+36-4a²+24a-36=2a²-6a

2) (2x²+x-5)²-(2x²+x)(2x²+x-1)+9(2x²+?)=?

3) (m²+n-4)²-(m²+n-1)(m²+n-8)=m⁴+2m²(n-4)+(n-4)²-m⁴-m²n+8m²-m²n-n²+8n+m²+n-8=

                                                       =m⁴+2m²n-8m²+n²-8n+16-m⁴-m²n+8m²-m²n-n²+8n+m²+n-8=

                                                       =m²+n+8